If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + y = 44 Solving 6x + y = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 6x + y + -1y = 44 + -1y Combine like terms: y + -1y = 0 6x + 0 = 44 + -1y 6x = 44 + -1y Divide each side by '6'. x = 7.333333333 + -0.1666666667y Simplifying x = 7.333333333 + -0.1666666667y
| y/z/z/t=1 | | 9-8N+3N=33-99 | | M-35=180 | | 231+3x=360 | | Ln(x)-x=Ln(0.05) | | 10x+1-1=70 | | 2.7x=0.3 | | 91-109=-8(-4Y)-17(2Y)+Y | | 4xsqure+8x=0 | | 3S=87 | | 13=n-12 | | x+8-7=3 | | 4y+-20x=-44 | | -270=-10(-3B) | | V-18= | | -40=3b+2b | | 105=-5(3Z) | | 84=7r+7r | | 29x+11y=19 | | =A+8 | | 4(5Z)=-100 | | -11M+3M=12-76 | | (4+9i)(4-9i)=equation | | 4K-6=2P+10 | | 4Y-9Y=25 | | 3(k+6)=3 | | -2-a=-28-3a | | -7n-4=4 | | -7n-4=3 | | (y^3-x^3)/xy^3 | | 4r+1g=34g-3r | | y^3-x^3/xy^3 |